The Effect Of Preview, Question, Read, Summarize Andtest (Pqrst) Strategy By Applying Wattpad Applicationon Students’ Achievement In Reading Comprehension At The Tenth Grade Sma Alwashliyah 07 Sei Rampah - Ardhana, Isnania; Zulkarnain, Iskandar; Rangkuti, Linda Astuti (English Education Study Program FKIP Universitas Alwashliyah Medan, 2024)
The objective of the study is to investigate if PQRST Strategy by applying Wattpad Application significantly affects students’ achievement in reading comprehension. This study was conducted by using experimental research design. The population of this study was the students of the tenth grade SMA Al Washliyah 07 Sei Rampah which had two parallel classes, namely X-1 and X-2. Each class consisted of 30 students. So, the total population was 60 students. In drawing the sample, Cluster Sampling Technique by applying Picker Wheel Technique was used in this research. After carrying out the Picker Wheel Technique, X-2 was selected as the experimental class and X-1 was selected as the control class. The experiment class was taught by using PQRST Strategy by applying Wattpad Application while the control class was taught without applying Wattpad Application. The instrument used in this study was reading test in the form of multiple-choice test. The data were analyzed by using t-test. After the data had been calculated, itwas found that t-observed was higher than t-table (11,61 > 2.00) with the degree of freedom df =58 at the level of significance α = 0.05. It meant that Ha was accepted and Ho was success fully rejected. In conclusion, PQRST Strategy by applying Wattpad Application Strategy significantly affects students’ achievement in reading comprehension.